Evaluation of metabolic profiles of Saanen goats in the transition period - AKKAYA, F.; SENTURK, S.; MECITOĞLU, Z.; KASAP, S.; ERTUNC, S.; KANDEMIR, C. (Journal of the Hellenic Veterinary Medical Society, 2020)
Healthy Saanen goats (n=30) in periparturient period were used in the present study. Blood samples were collected 21, 14 and 7 days before parturition, at the time of birth and postpartum days 7, 14 and 21. Non-esterifiedfatty acids (NEFA), betahydroxy butyric acid (BHBA), Total protein (TP), albumin (ALB), blood urea nitrogen (BUN), creatinine (CREA) aspartate amino transferase (AST), gamma glutamyl transferase (GGT), sorbitol dehydrogenase (SDH), glucose (GLU), cholesterol (CHOL), triglyceride (TG), calcium (Ca), phosphorus (P), and magnesium (Mg) levels were evaluated. During the study period, NEFA, SDH, CREA levels increased and CHOL and TG levels decreased at time of parturition. When the changes of parameters in prepartum and postpartum period were compared, the concentrations of NEFA, CHOL, GLU, TG, Ca were higher (p <0.001) in prepartum period;however BHBA, Mg, ALB, GGT, AST, TP, P, BUN, SDH and CREA concentrations were detected to be higher (p <0.001) in postpartum period. Metabolic Profile Test based on biochemical parameters evaluated in our study would be beneficial for diagnosis, prevention and control of diseases such as pregnancy toxemia, hypocalcemia, infertility in goats.